Modification of Sea Water Scrubber System into Fresh Water of Inert Gas System on the Crude Oil Tanker 85,000 DWT - Nurhadi Siswantoro; Hari Prastowo; Faris Zulfar Rosyadi (International Journal of Marine Engineering Innovation and Research, 2020)
Each ship carrying a hydrocarbon must be equipped with an inert gas system. On tankers, the function of inert gas is to prevent fires or explosions caused by oxygen levels contained in cargo tanks. Inert gas is produced by cleaning the exhaust gas boiler using a sea water scrubber system. However, seawater has corrosive properties that cause the use of material in scrubber system components to be resistant to corrosion. Therefore, through this research a modification of the sea water scrubber system was made into a freshwater scrubber system. The advantages of a freshwater scrubber system include a low corrosive level that causes the use of inexpensive materials. Modification of seawater scrubber systems into fresh water causes additional components to be made, including adding NaOH tank, expansion tank of freshwater, seawater pumps, freshwater pumps, NaOH pumps, heat exchanger, and wash water treatment unit. Economic calculations are carried out to determine the installation costs and operational costs needed from this modification. Based on the technical and economical analysis, modification of the sea water scrubber system into fresh water inert gas system of Crude Oil Tanker 85,000 DWT can be done with an estimated installation cost of 1.5 Bill. Rupiahs.